Mental health and breastfeeding behavior in early postpartum mothers: A cross-sectional study - Anita Dewi Lieskusumastuti; Mudfdlilah; Sri Ratna Ningsih (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Breastfeeding in the early postpartum period is critical for maternal–infant health, yet maternal psychological conditions may influence breastfeeding practices. This study aimed to examine the association between maternal mental health status and breastfeeding behavior among early postpartum mothers at PKU Muhammadiyah Delanggu Hospital, Indonesia. Research Methodology: A quantitative descriptive–analytic study with a cross-sectional design was conducted during June–July 2023. A total of 65 early postpartum mothers were recruited using accidental (convenience) sampling. Maternal mental health was assessed using the Depression Anxiety Stress Scale-21 (DASS-21), while breastfeeding behavior was measured using a validated questionnaire and LATCH observation. Data were analyzed using univariate statistics and the chi-square test with a significance level of 0.05. Results: Overall, 50.8% of mothers had good mental health, and 58.5% demonstrated positive breastfeeding behavior. A significant association was found between maternal mental health and breastfeeding behavior (χ² test, p = 0.018). Mothers with good mental health were more likely to exhibit positive breastfeeding behavior compared with those with poorer mental health (36.9% vs 21.5%). Conversely, negative breastfeeding behavior was higher among mothers with poorer mental health (27.7% vs 13.8%). Conclusion: Maternal mental health is significantly associated with breastfeeding behavior in the early postpartum period. Integrating routine mental health screening into postpartum care may improve breastfeeding outcomes and support maternal well-being.